The state and prospects of development of free economic zones in the Republic of Uzbekistan - G. Ubaydullaeva; Bekhzod Ravshanov (Zien Journals, 2022)
The article discusses the foreign experience in improving the functioning of free economic zones. In addition, measures to implement a foreign strategy in Uzbekistan were considered.
Keywords: free economic zone; investment; tax incentives